2021
DOI: 10.18332/ejm/134846
|View full text |Cite
|
Sign up to set email alerts
|

Maternity ward staff perceptions of exclusive breastfeeding in Finnish maternity hospitals: A cross-sectional study

Abstract: INTRODUCTION This study aimed to describe exclusive breastfeeding (EBF, Step 6 of the Baby-Friendly Hospital Initiative) in Finnish maternity hospitals and identify factors that promote or limit EBF. METHODS A cross-sectional study design was used, and data were collected from eight maternity hospitals in Finland during a 10-day period in May 2014. The staff completed questionnaires (n=1554) from separate work shifts. The data were analyzed using descriptive statistics, and chi-squared and Fisher's tests. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…Midwifes could influence and increase breastfeeding rates by training women how to understand the whole process and nature of breastfeeding, outcomes that have been proved similarly and in our study using our intervention protocol [15,[55][56][57][58]. More specifically, individualized education in low-risk women and women with endocrine diseases of midwifery staff as in our study, proved to be effective in accordance with the published evidence, as it reduces the likelihood of cessation of breastfeeding, and increases women's knowledge, skills and confidence in breastfeeding [39,59].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Midwifes could influence and increase breastfeeding rates by training women how to understand the whole process and nature of breastfeeding, outcomes that have been proved similarly and in our study using our intervention protocol [15,[55][56][57][58]. More specifically, individualized education in low-risk women and women with endocrine diseases of midwifery staff as in our study, proved to be effective in accordance with the published evidence, as it reduces the likelihood of cessation of breastfeeding, and increases women's knowledge, skills and confidence in breastfeeding [39,59].…”
Section: Discussionsupporting
confidence: 82%
“…Personalized education and support are likely to increase breastfeeding initiation, exclusivity and duration rates [37][38][39]. Previous studies showed that social factors and targeted intervention in the prenatal or postnatal period might have a positive effect on the onset and duration of breastfeeding, increase confidence in breastfeeding and provide women with adequate knowledge about breastfeeding and increase exclusive breastfeeding [40][41][42][43][44][45][46][47][48][49].…”
Section: Interventions To Support Breastfeedingmentioning
confidence: 99%
“…Therefore, it is not surprising that a higher proportion of mothers, even for those with cesarean delivery, reported that they had skin-to-skin contact immediately after birth, rooming-in with their infants, breastfeeding initiation within the first hour and EBF during hospitalization in our study. These interventions have all been shown to be strong contributors to establishment and continuation of breastfeeding [ 7 , 14 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is not surprising that a higher proportion of mothers, even for those with cesarean delivery, had skin-to-skin contact immediately after birth, rooming-in with their infants, breastfeeding initiation within the rst hour and EBF during hospitalization in this survey. These interventions have been shown to be strong contributors to establishment and continuation of breastfeeding [11,[17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of associations of other variables with EBF within six months may be due to the fact that the majority of surveyed mothers were employed and had breastfeeding initiation within the rst hour. As for mode of delivery, previous studies have suggested that women with cesarean delivery were less likely to EBF than those with vaginal delivery [6,17]. Delayed onset of lactation, disrupted mother-infant interaction, inhibited infant suckling and poor pain relief may mediate the effects of caesarean delivery on breastfeeding [25].…”
Section: Discussionmentioning
confidence: 99%